Strengthen the sacral ligament and paravagina by equilibrium control severe pelvic organ prolapse - Zhao, Xin; Niu, Jumin; Liu, Yansong (Frontiers in Surgery, 2023)
Abdominal sacrocolpopexy is the gold standard for treating pelvic organ prolapse(POP) because of safety and durable good results.Morerecently laparoscopic sacrocolpopexy(LSC),a less invasive approach,has become popular.Although these surgeries are versatile and can treat almost all patients with POP,these techniques have shortcomings.Speciﬁcally,reinforcement of lateral vaginal defects are not very strong,thus patients with POP and a severe paravaginal defect are not good candidates for abdominal or laparoscopic sacrocolpopexy.To overcome this problem, we demonstrate the combination between LSC, sacral ligament fusion, vaginal suspension in order to enhance both Level 1 and 2 while strengthen Level 3 by the original anterior-posterior colporrhaphy,which can reinforce severe paravaginal defects.It controls pelvic organ prolapse equilibrium.